Pengaruh Konsentrasi Dan Waktu Aktivasi Adsorben Spent Bleaching Earth (SBE) Terhadap Luas Permukaan - Ulfah Nurulita; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Spent bleaching earth (SBE) is solid waste that is produced from the bleaching industry of palm oil (CPO). In principle, SBE can be regenerated and reused as an adsorbent, but its adsorption capability is limited. This weakness can be overcome through an activation process using one type of mineral acid such as hydrochloric acid (HCl). HCl as a chemical activator can reduce the moisture content in the resulting adsorbent and can dissolve impurities so that more adsorbent pores are formed. This study aims to determine the effect of the effect on HCl concentration and contact time of iodine activation number and SBE surface area. Keywords: Adsorbent, Activation, HCl, Spent Bleaching Earth.